2009
DOI: 10.1073/pnas.0910964106
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical model for gamma rhythms in the olfactory bulb via subthreshold oscillations

Abstract: Gamma oscillations in the olfactory bulb can be produced as an interaction of subthreshold oscillations (STOs) in the mitral cells (MCs) with inhibitory granule cells (GCs). The mechanism does not require that the GCs spike, and we work in a regime in which the MCs fire at rates lower than the fast gamma rhythm they create. The frequency of the network is that of the STOs, allowing the gamma to be modulated in amplitude with only small changes in frequency. Gamma oscillations could also be obtained with spikin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
88
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(93 citation statements)
references
References 33 publications
(54 reference statements)
5
88
0
Order By: Relevance
“…Modulatory inputs on mitral and granule cells can potentially affect the dynamics of neural activity as well as spike timing and degrees of synchronization. Levels of synchronization among bulbar outputs have been proposed to contribute to odor processing and learning experimentally (Beshel et al 2007;Brea et al 2009;Kay et al 2009;Nusser et al 2001). Modulatory inputs to granule and mitral cells can potentially regulate oscillatory dynamics of olfactory bulb processing and hence change the processing of odors, as proposed early on by Freeman and colleagues (Di Prisco and Freeman 1985;Gray et al 1986) and shown recently in slices of young rats by Schoppa and colleagues (Gire and Schoppa 2008;Pandipati et al 2010).…”
Section: Olfactory Bulb Network and Processingmentioning
confidence: 94%
“…Modulatory inputs on mitral and granule cells can potentially affect the dynamics of neural activity as well as spike timing and degrees of synchronization. Levels of synchronization among bulbar outputs have been proposed to contribute to odor processing and learning experimentally (Beshel et al 2007;Brea et al 2009;Kay et al 2009;Nusser et al 2001). Modulatory inputs to granule and mitral cells can potentially regulate oscillatory dynamics of olfactory bulb processing and hence change the processing of odors, as proposed early on by Freeman and colleagues (Di Prisco and Freeman 1985;Gray et al 1986) and shown recently in slices of young rats by Schoppa and colleagues (Gire and Schoppa 2008;Pandipati et al 2010).…”
Section: Olfactory Bulb Network and Processingmentioning
confidence: 94%
“…These studies pay less attention to the role of intrinsic cellular properties or the impact of more varied network structures, as the conceptual PING mechanism assumes strong E-I and I-E inter-connectivity as well as strong I-I intra-connectivity and burst frequencies are presumed to be dictated by properties of synaptic currents. However, as our biological understanding of the brain rapidly accelerates, the immense diversity of neuron properties, particularly of inhibitory interneurons, and network connectivities among these interneuron populations (Brea et al 2009;Kopell et al 2010;Best et al 2007;Klausberger et al 2003;Buhl et al 1994;Beierlein et al 2000;Barthó et al 2004;Somogyi and Klausberger 2005;Klausberger and Somogyi 2008;Gonchar and Burkhalter 1997;Beierlein et al 2003;Gibson et al 1999;Deco and Thiele 2011;Hasselmo and Giocomo 2006;Hasselmo and Sarter 2011;Sarter et al 2005) motivates computational research to investigate and understand dynamics arising from the interaction of cellular properties and network connectivity structures.…”
Section: Discussionmentioning
confidence: 99%
“…Given the paramount effect cholinergic modulation has on intrinsic cellular properties and a neuron's tendency to exhibit synchrony, here we investigate its influence on the synchronous dynamics of networks of inter-connected excitatory and inhibitory neurons (E-I networks), as such networks are ubiquitous in the brain (Brea et al 2009;Kopell et al 2010;Best et al 2007). The interactions of excitatory and inhibitory neurons can generate oscillatory bursts of synchronous spiking of excitatory cells which underlie rhythmic electrical activity observed in electroencephalogram (EEG) recordings associated with different brain states and cognition (Cannon et al 2014;Whittington et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…For example [1], biophysical models to explain the gamma band oscillation in the olfactory bulb based on coupled subthreshold oscillators have been shown to exhibit synchronisation and coherence effects when driven with correlated inputs. Similarly, in recent models of temporal coding [2], competition for coherence driven by increased phase velocity of neural units in cases of coherent input from the connected neurons leads to different perspectives on assembly formation in collections of coupled oscillator neurons.…”
Section: Introductionmentioning
confidence: 99%